Paycheck [videorecording (DVD)] - Affleck, Ben, 1972-; Eckhart, Aaron; Thurman, Uma; Giamatti, Paul; Dick, Philip K. (Full screen DVD collection, 2004)
Jennings is the best reverse-engineer in the business. He is hired by his friend Rethrick to do a special job, with the promise of a multi-million dollar paycheck when successfully completed. When he is finished, all memory of what he had been working on is erased from his mind. That's when his problem really start to begin. He is hunted by the FBI for something he has no recollection of doing and has little time to work it out. Before his memory wipe, he sent himself 19 seemingly unconnected objects, to allow him to put the puzzle together and discover just what has gone on and what he has done.